“Osteogenesis Imperfecta, Type Xvii” - A Rare Genetic Entity - Saini, Jitendra; T Nair, Bindu; Swarup, Praneta; Kumar, Pradeep (Journal of Neonatal Surgery, 2025)
Introduction: Osteogenesis imperfecta (OI) is a genetic disorder with the incidence of 1 in 15,000 to 20,000 births. Around 85%–90% are dominant mutations in collagen type I α1 (COL1A1) or COL1A2 genes, while a plethora of other genes have been associated with non-collagen OI in recent years. Osteogenesis imperfecta type XVII is described as an autosomal recessive form which is rare, occurring due to mutation in SPARC gene on chromosome 5q33, characterized by bone deformity, significant reduction of bone density and short stature. Case Report: A 7 year male child product of non-consanguinous marriage presented with complaints of multiple bony deformities in the form of forward bowing of bilateral lower limbs, outward bowing of bilateral upper limbs, suggestive of multiple fracture lines and severe osteopenia along with thinned out cortex on skeletal survey. Although metabolic profile was normal. Child also had short stature and cross bite teeth. Child was diagnosed to have OI based on characteristic clinico-radiological features and thereafter whole genome sequencing was done to know the subtype. Whole genome sequencing was suggestive of Osteogenesis imperfect type XVII (SPARC mutation) on Exon 9. Conclusion: This case is being reported because of the rarity of OI type 17 especially in Indian population. Besides, the aim was also to review the literature to highlight the challenges and recent advances in the management. There is a great need for further research to decrease the morbidity associated with this disease and also to find a cure for the same.